SOCIAL SUPPORT PERCEPTION AND SUCCESSFUL AGING AMONG JAVANESE PEOPLE - Diah Karmiyati (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2017)
The objective of this research was to obtain a correlation between social support perception and successful aging among elderly Javanese people. This research was conducted by using quantitative correlational design. The method was intended to determine the contribution social support on successful aging. Subject of this research was the elderly whose the member of some elderly organization in Solo and Malang. The sampling technique used was purposive sampling based on the prescribed criteria of research subjects. Then, the collected data were then analyzed by using Pearson Correlation Method. The findings of this research showed that there was a significance positive correlation between social support perception and successful aging among Javanese people.